Effect Of Coating Condition On The Corrosion Properties Of Mild Steel Substrate - Khairul Nizam, Zainuddin (UTeM, 2009)
Corrosion is a one problem that encountered in industry particularly against steel. There is much prevention and solution that researches and engineers applied in order to stop this problem from occurring in the future. In this project, the corrosion prevention of tin electroplating is carried out on the mild steel with several specimens. The implementation of this project is done with all the specimens are through surface preparation for electroplating, electroplating process with various coating parameters, determination of thickness coating, surface morphology examination before and after specimens corroded by using scanning electron microscope and followed by determination of corrosion rate based on Tafel extrapolation. The standard for preparation of tin electroplating is according to the ASTM B545, surface preparation referred to the ASTM B183 and corrosion rate measurement referred to the ASTM G102. The parameters that involved are current density of coating, times and constant of solution bath. As a result, the best parameter is determined which from current density of 6 A/dm² and 10 minutes of coating time. This parameter also capable to give a less of corrosion rate both condition of coating which are scratched coating and unscratched coating. The lower of current density is promoting the formation of tin whiskers and thin of coating but it gives a less of corrosion rate. The higher of current density promotes formation of cracking and worst of corrosion rate.